1999
DOI: 10.1104/pp.120.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of a Plant Small Heat-Shock Protein Enhances Escherichia coliViability under Heat and Cold Stress1

Abstract: A small heat-shock protein (sHSP) that shows molecular chaperone activity in vitro was recently purified from mature chestnut (Castanea sativa) cotyledons. This protein, renamed here as CsHSP17.5, belongs to cytosolic class I, as revealed by cDNA sequencing and immunoelectron microscopy. Recombinant CsHSP17.5 was overexpressed in Escherichia coli to study its possible function under stress conditions. Upon transfer from 37°C to 50°C, a temperature known to cause cell autolysis, those cells that accumulated CsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 41 publications
5
93
1
5
Order By: Relevance
“…In mammalian cells, sHsp expression confers increased thermotolerance, as does expression of plant class I sHsp or ␣B-crystallin in E. coli (36,37). More interestingly, expression of sHsp from chestnut (Castanea sativa) in E. coli enhanced cell viability not only to heat stress but also to low temperature (4°C) (38). Clearly, these findings fundamentally question the view that the ability of sHsps to attenuate both heat-and cold-induced cell injury is solely due to their chaperone function.…”
Section: Discussioncontrasting
confidence: 43%
“…In mammalian cells, sHsp expression confers increased thermotolerance, as does expression of plant class I sHsp or ␣B-crystallin in E. coli (36,37). More interestingly, expression of sHsp from chestnut (Castanea sativa) in E. coli enhanced cell viability not only to heat stress but also to low temperature (4°C) (38). Clearly, these findings fundamentally question the view that the ability of sHsps to attenuate both heat-and cold-induced cell injury is solely due to their chaperone function.…”
Section: Discussioncontrasting
confidence: 43%
“…1), as expected because high temperature is the classic inducer of sHSP, suggesting that CeHSP17 may play an important role in preventing the natural host from thermal stress damage or may assist to repair the damages caused by such thermal insult. Similarly, C. elegans HSP16 (Dixon et al, 1990) and other sHSP from mammalian cells (Landry et al, 1989), plants (Soto et al, 1999;Basha et al, 2004), and prokaryotes (Torok et al, 2001) have been demonstrated to be induced by heat, and correlated with protection against thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that both ␣B-crystallin and mammalian HSP27 provide protection against ischemic injury in cardiac myocytes (11). Several experiments support a role for sHSPs in the acquisition of thermotolerance in mammalian cells, yeast, plants, and prokaryotes (6,12,13). A causal link between the level of sHSPs and thermotolerance in a cyanobacterium, Synechocystis sp.…”
mentioning
confidence: 99%